Director Accountability and the Mediating Role of the Corporate Board - Margaret M. Blair; Lynn A. Stout (Washington University Law Quarterly, 2001)
One of the most pressing questions facing both corporate scholars and businesspeople today is how corporate directors can be made accountable. Before addressing this issue, however, it seems important to consider two antecedent questions: To whom should directors be accountable? And for what?
Keywords: Corporate governance; Executives; Corporate directors; Corporation law; Securities law; Stockholders